Characteristics and mixing state of amine-containing particles at a rural site in the Pearl River Delta, China - C. Cheng (Atmospheric Chemistry and Physics, 2018)
Particulate amines play an important role for the particle acidity and hygroscopicity and also contribute to secondary organic aerosol mass. We investigated the sources and mixing states of particulate amines using a single-particle aerosol mass spectrometer (SPAMS) during summer and winter 2014 at a rural site in the Pearl River Delta, China. Amine-containing particles accounted for 11.1 and 9.4 % of the total detected individual particles in summer and winter, respectively. Although the increase in amine-containing particle counts mostly occurred at night, no obvious correlations between amine-containing particles and ambient relative humidity (RH) were found during the sampling period. Among the three markers we considered, the most abundant amine marker was 74(C2H5)2NH2+, which was detected in 90 and 86 % of amine-containing particles in summer and winter, followed by amine marker ions of 59(CH3)3N+, and 86(C2H5)2NCH2+ which were detected in less than 10 % of amine-containing particles during sampling period. The amine-containing particles were characterized by high fractions of carbonaceous marker ions, carbon–nitrogen fragments, sulfate, and nitrate in both summer and winter. More than 90 % of amine-containing particles were found to be internally mixed with sulfate throughout the sampling period, while the percentage of amine particles containing nitrate increased from 43 % in summer to 69 % in winter. Robust correlations between the peak intensities of amines, sulfate, and nitrate were observed, suggesting the possible formation of aminium sulfate and nitrate salts. Interestingly, only 8 % of amine particles contained ammonium in summer, while the percentage increased dramatically to 54 % in winter, indicating a relatively ammonium-poor state in summer and an ammonium-rich state in winter. The total ammonium-containing particles were investigated and showed a much lower abundance in ambient particles in summer (3.6 %) than that in winter (32.6 %), which suggests the ammonium-poor state of amine-containing particles in summer may be related to the lower abundance of ammonia/ammonium in gas and particle phases. In addition, higher abundance of amines in ammonium-containing particles than that of ammonium in amine-containing particles suggests a possible contribution of ammonium–amine exchange reactions to the low abundance of ammonium in amine-containing particles at high ambient RH (72 ± 13 %) in summer. The particle acidity of amine-containing particles is estimated via the relative acidity ratio (Ra), which is defined as the ratio of the sum of the sulfate and nitrate peak areas divided by the ammonium peak area. The Ra was 326 ± 326 in summer and 31 ± 13 in winter, indicating that the amine-containing particles were more acidic in summer than in winter. However, after including amines along with the ammonium in the acidity calculation, the new Ra′ values showed no seasonal change in summer (11 ± 4) and winter (10 ± 2), which suggests that amines could be a buffer for the particle acidity of ammonium-poor particles.